Greek religion and cults in the Black Sea Region goddesses in the Bosporan Kingdom from the Archaic Period to the Byzantine Era - Braund, David 1957- (Cambridge University Press, 2018)
Cover -- Half-title -- Title page -- Copyright information -- Table of contents -- List of illustrations -- List of maps -- Preface -- Introduction: Aims, Contexts and Connectivity -- Chapter 1 Crimean Parthenos, Artemis Tauropolos and Human Sacrifice -- Bosporan Parthenos: Porthmium and Parthenium -- Parthenos at the Crossing: Deer-Hunters and a Mad Cow -- Chryse near Parthenium -- Talking to Taurians: Parthenos, Iphigenia and Achilles -- Parthenos between Taurians and Greeks -- Taurian Identity and the Extent of the Kizil Koba Culture -- Iphigenia and Achilles -- Parthenos at Panticapaeum and Nymphaeum? -- Parthenos in Chersonesus -- Gykia's Story -- Conclusions -- Chapter 2 Crimean Parthenos in Greece, Anatolia and the Mediterranean World -- Athens: From the Taurians to Halae and Brauron -- Sparta -- Syria -- Between Lake Nemi and Asia Minor -- Conclusions -- Chapter 3 Artemis of Ephesus in the Bosporan Kingdom -- The Bosporan Evidence: Ephesia and Agrotera -- Ephesian Colonisation? -- The Attractions of Artemis Ephesia in the Bosporus and Beyond -- Conclusions -- Chapter 4 Bosporan Isis -- Demeter and Argive Io: Herodotus and the Many Greek Faces of Isis -- Bosporan Io and Prometheus Bound -- Bosporan Outlooks: Io and Osiris -- Isis the Trireme -- Bosporans in Egypt, 254 bc -- Conclusion -- Chapter 5 The 'Mistress of Apatouron': Aphrodite Ourania and the Bosporan Apatouria -- Approaching Aphrodite Ourania -- Approaching Bosporan Ourania: Origins and Imaginings -- Mythmaking and Public Performance in the Bosporus -- Sosicrates and Sostratus, Writers of Phanagoria -- Myth, Landscape, Cult -- Locating Apatouron -- The Epigraphic Record -- Deceitful Aphrodite and the Bosporan Apatouria -- Coinage, Wealth, Ritual -- Bosporan Ourania and the Roman Imperial Cult -- Chapter 6 Epilogue: Artemis, Aphrodite and Demeter
Keywords: Griechisch; Religion; Antike; Göttin; Kult; Bosporanisches Reich; Schwarzmeer-Gebiet